Syringe exchange programs in Brazil: preliminary assessment of 45 programs - Elize Massard da Fonseca; José Mendes Ribeiro; Neilane Bertoni; Francisco I. Bastos
The present study aims to evaluate the current operation of Brazilian syringe exchange programs (SEP). After consulting national and regional networks of people working in projects/ programs aiming to reduce drug-related harm, we identified 134 potential participant programs. Unfortunately, only 45 SEPs answered a survey, even after repeated attempts. The survey addressed: coverage, funding, procurement of basic supplies, managerial capacity, and the local political environment. Findings were triangulated with in-depth interviews with key informants. The main findings included: satisfactory adherence to the initiatives and adequate documentation, but deficiencies in terms of coverage and monitoring, and uneven procurement of resources. Program personnel work mostly on a provisional basis, despite the efforts of local coordinators. Most programs are funded by the National STDs/AIDS Program. A comprehensive agenda aiming to improve current operations should include: concerted efforts to improve local and regional databanks, incentives/sanctions toward full accountability of initiatives carried by the programs, and a genuine culture of monitoring and evaluation.